Transforming Cities Through Renewable Energy: Analyzing the Role of Green Infrastructure in Driving Urban Economic Growth - Muhammad Ade Kurnia Harahap; Jeffriansyah Dwi Sahputra Amory; Muh. Ilhamuddin Dahri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Cities worldwide are experiencing rapid population growth, leading to increased demand for energy, transportation, and other infrastructure. This poses significant challenges in providing sustainable and environmentally friendly energy. This research aims to analyze the role of green infrastructure in driving urban economic growth through the implementation of renewable energy. The method used in this study is a literature review with a qualitative approach. Data were collected from articles published on Google Scholar between 2013 and 2024. The study results indicate that the use of renewable energy and the development of green infrastructure play a crucial role in transforming cities towards sustainability. The main findings show that renewable energy has a positive impact on reducing carbon emissions, while green infrastructure improves the quality of life and drives urban economic growth. Cities in Indonesia, such as Bandung, Surabaya, and Jakarta, have provided tangible examples of success in implementing these strategies.